Epilepsy management in older people: Lessons from National Audit of Seizure management in Hospitals (NASH). (August 2017) - Ziso, B.; Dixon, P.A.; Marson, A.G.
Highlights: Older patients presenting with seizures are more likely to be admitted to hospital and have imaging. Older patients are less likely to be referred to epilepsy or specialist services on discharge. There appears to be significant disparity in patient age and rate of referral to epilepsy or specialist services. Abstract: Purpose: Epilepsy is the third most common diagnosis in older people, however management in this group remains variable. National Audit of Seizure management in Hospitals (NASH) set out to assess care provided to patients attending hospitals in England following a seizure. Method: 154 Emergency Departments (EDs) across the UK took part. 1256 patients aged 60 years or over were included for analysis (median age 74 years, 54% men). 51% were known to have epilepsy, 17% had history of previous seizure or blackout and 32% presented with a suspected first seizure. Results: 14% of older patients with epilepsy were not on treatment, 59% were on monotherapy. Sodium valproate was the most commonly used antiepileptic, 28%. 35% of patients with epilepsy, aged 60 and over, had a CT during admission compared to only 17% of those under 60. 80% of patients aged 60 and over presenting with a likely first seizure were admitted to hospital, compared to 65% of those under 60. 34% of those with suspected first seizure were referred to a neurologist on discharge compared to 68% of patients under the age of 60. 52% of 60–69 year olds with a suspected first seizure were referred to neurology compared to 25% of patients aged 80-89. Conclusions: Older patients presenting with seizures are more likely to be admitted to hospital and have imaging. They are less likely to be referred to specialist services on discharge. There appears to be significant disparity in patient age and rate of referral.